Haploidentical Hematopoietic Stem-cell Transplant for High-Risk Acute Myeloid Leukemia in a Kidney Transplant Recipient: Case Report - Amorim Mota Segundo, Hercules; Magalhães Chaves, Ana Vitoria; Araújo Freire de Sá, Thays; Sampaio Nunes Barroso, Karine; Messias de Araújo Filho, Raimundo; Frassinetti Castelo Branco Camurça Fernandes, Paula; Barroso Duarte, Fernando (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Solid organ transplantation is associated with a higher incidence of malignancies. Among them, acute myeloid leukemia has high morbidity and mortality, and its cure is only possible through allogeneic hematopoietic stem cell transplantation for high-risk disease. Case report: A 32-year-old female who underwent a kidney transplant eight years before was diagnosed with high-risk acute myeloid leukemia. She underwent induction therapy with “7+3”, achieving complete remission with measurable residual disease detectable by flow cytometry. She then underwent a myeloablative haploidentical allogeneic transplant, achieving complete remission, free of graft-versus-host disease, with a functioning renal graft.